Impacto da ressecção profunda de focos de endometriose em compartimento posterior da pelve sobre parâmetros urodinâmicos - FARIAS, Jardel Cavalcante de (2021)
Endometriosis is an inflammatory disease characterized by the presence of endometrial tissue outside the uterine cavity and develops mainly in the pelvis. The most common symptoms are dysmenorrhea, chronic pelvic pain, and dyspareunia. Laparoscopy for surgical removal is the first-line treatment for endometriosis. The study aimed to evaluate the impact of deep resection of endometriosis foci in the posterior compartment of the pelvis on urodynamic parameters. This is a prospective and observational study carried out between January 2019 and January 2021 that evaluated 34 women with deep endometriosis in the posterior compartment of the pelvis. Sociodemographic questionnaires, ICIQ-FLUTS, and urodynamic study tests were applied, the last two applied one month before and three after the surgical procedure. The patients underwent laparoscopic surgery with nerve preservation and were divided into two groups, the first of patients with Deep Infiltrative Endometriosis of posterior compartment restricted to the uterosacral ligaments (USL) and the second with lesions of posterior involvement of wider distribution, involving USL and also endometriosis of rectovaginal septum and rectal lesion smaller than 3 cm (USL + SEPT). To compare moments pre (T0) and post-intervention (T1), Wilcoxon tests were used in numerical variables and McNemar in categorical variables. To compare variables between surgical techniques, Student's t-test or Mann-Whitney test was applied for numerical variables and Chi-Square for categorical variables. The uroflowmetry data show that there was a trend in both groups towards increased sensitivity, but with improvement after the surgical procedure. There was no change in maximal cystometric capacity either preoperatively or postoperatively. In the other parameters, no flow changes were found, as well as statistically significant differences at different times. In the evaluation of pressure parameters, a low bladder pressure was identified in the maximum cystometric capacity in the USL + EPS group at time T0, even with a statistically significant difference concerning the USL group at the same time T1. The urinary function questionnaire showed that all parameters evaluated (filling, voiding, and incontinence) presented reduced scores after surgical intervention, with a statistically significant difference when were evaluated the groups together. In our findings, there was no difference in urodynamic parameters in the different pre and post-intervention groups, but there was a significant response in the perception of quality of urinary function, mainly related to sensitivity and bladder emptying. And in the end, there was a marked reduction in urinary symptom scores in the different groups after the advent of surgery.